The archaeology of Anatolia. - Steadman, Sharon R.; McMahon, John Gregory, 1953- (Cambridge Scholars Publishing, 2021)
This fourth volume in the Archaeology of Anatolia series offers reports on the most recent discoveries from across the Anatolian peninsula. Periods covered span the Epipalaeolithic to the Medieval Age, and sites and regions range from the western Anatolian coast to Van, and on to the southeast. The breadth and depth of work reported within these pages testifies to the contributors' dedication and love of their work even during a global pandemic period. The volume includes reviews of recent work at on-going excavations and data retrieved from the last several years of survey projects. In additi.